2007
DOI: 10.1038/sj.cgt.7701077
|View full text |Cite
|
Sign up to set email alerts
|

Development of human umbilical cord matrix stem cell-based gene therapy for experimental lung tumors

Abstract: Umbilical cord matrix stem (UCMS) cells are unique stem cells derived from Wharton's jelly, which have been shown to express genes characteristic of primitive stem cells. To test the safety of these cells, human UCMS cells were injected both intravenously and subcutaneously in large numbers into severe combined immunodeficiency (SCID) mice and multiple tissues were examined for evidence of tumor formation. UCMS cells did not form gross or histological teratomas up to 50 days posttransplantation. Next, to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 33 publications
(40 reference statements)
5
118
0
4
Order By: Relevance
“…It has been shown convincingly that stem cells have the ability to traffic to tumors, and signals that mediate this effect seem to be similar or identical to those that mediate recruitment of stromal or defensive cells in tumors (1)(2)(3). There are also a number of reports showing that genetically engineered stem cells efficiently deliver therapeutic proteins to cancer and other sites of inflammation (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown convincingly that stem cells have the ability to traffic to tumors, and signals that mediate this effect seem to be similar or identical to those that mediate recruitment of stromal or defensive cells in tumors (1)(2)(3). There are also a number of reports showing that genetically engineered stem cells efficiently deliver therapeutic proteins to cancer and other sites of inflammation (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…They were engineered to express human interferon beta and were administered intravenously into SCID mice bearing tumours. This treatment significantly reduced the tumour burden (Rachakatla et al 2007). Similarly, human umbilical cord blood-derived MSCs (UCB -MSCs) have been used to deliver a secretable trimeric form of tumour necrosis factor-related apoptosis-inducing ligand (stTRAIL), via adenoviral transduction mediated by cell-permeable peptides, to human glioma cells in nude mice.…”
Section: Cancer Therapymentioning
confidence: 99%
“…It thus appears that the cell fragment-mediated transfer of adenovirus is independent of adenovirus receptors and is not blocked by anti-adenovirus antibodies. Many studies of oncolytic virus-infected carrier cell systems have been reported in oncolytic HSV-1 mutant-infected PA-1 cells (7), in modified vaccinia virus-infected cytokine-induced killer (CIK) cells (11), in oncolytic adenovirus-infected A549 cells (15), in vesicular stomatitis virus (VSV)-infected colon carcinoma cells (13), in nerve growth factor-transduced autologous fibroblasts (19), and in human interferon ß-transduced umbilical cord matrix stem cell (20). In this study, AdE3-IAI.3B selectively killed OSCC cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%